Hyponatremic Seizures and Adrenal Hypoplasia Congenita in a Neonate with Congenital Diaphragmatic Hernia - Sourabh Verma; Sheryl Purrier; Emily Breidbart; John G. Pappas; Pradeep V. Mally; Tara M. Randis (Hindawi Limited, 2019)
Congenital diaphragmatic hernia (CDH) in neonates may occur as an isolated finding, in association with other anomalies, or as part of a genetic syndrome. We report the first case of an infant with CDH who presented with hyponatremic seizures due to adrenal hypoplasia congenita (AHC). The patient underwent repair of CDH defect. After an uncomplicated postoperative course while on discharge planning, he developed a seizure episode associated with severe hyponatremia and hyperkalemia. Extensive diagnostic workup revealed an NR0B1 gene variant confirming the diagnosis of X-linked AHC. The patient was eventually discharged home on hydrocortisone, fludrocortisone, and salt supplements. There are a few case reports of adrenal insufficiency in neonates with CDH, manifesting with symptoms before and immediately after reparative surgery. Clinical presentation of our patient was unique in manifesting as neonatal seizure secondary to severe hyponatremia after a stable postoperative phase. The patient's electrolytes and hemodynamic status remained stable before, during, and after surgery for CDH. This case underlines the importance of taking detailed family history and continued vigilance for signs and symptoms of adrenal insufficiency in infants with repaired CDH by pediatricians and intensivists.